Luminescent Pt–Ag Clusters Based on Neutral Benzoquinolate Cyclometalated Platinum Complexes1. Issue 12 (12th February 2013) - Martín, Antonio; Belío, Úrsula; Fuertes, Sara; Sicilia, Violeta
Abstract: Complexes of the type [Pt(C6 F5 )(bzq)L] bzq = 7, 8‐benzoquinolinate; L = PPh3 (2 ), 2, 6‐diphenylpyridine (pyPh2, 3 ), tetrahydrothiophene (tht, 4 ), MeCN (5 ) were prepared by replacing the acetone ligand in [Pt(C6 F5 )(bzq)(Me2 CO)] (1 ) with the corresponding L ligand. The structures of complexes2 –4 were established by X‐ray diffraction. Despite their neutral nature, complexes1 –5 react with AgClO4 in a 2:1 molar ratio to give the corresponding trinuclear complexes [Pt(C6 F5 )(bzq)L2 Ag]ClO4 L = Me2 CO (6 ), PPh3 (7 ), pyPh2 (8 ), tht (9 ), MeCN (10 ), which contain Pt → Ag dative bonds. The structures of complexes7, 9, and10 were established by X‐ray diffraction, which confirmed the existence of Pt–Ag bonds (ca. 2.8 Å) and short η 1 bonding Ag–C interactions with the C ipso atom of bzq (ca. 2.4 Å). Moreover, complexes3, 4, 7, 9, and10 show intermolecular π··· π interactions between the aromatic rings of the bzq ligands (separations of ca. 3.5 Å). The reactions of1 –5 with [Ag(PPh3 )(OClO3 )] in a 1:1 molar ratio proceed with interchange of the ligands between the metals and the formation of [Pt(bzq)(C6 F5 )(PPh3 )2 Ag]ClO4 (7 ) and [AgL2 ]ClO4 (X‐ray). Only in the case of L = pyPh2 (3 ) was the dinuclear complex [(C6 F5 )(bzq)(PPh3 )PtAg(pyPh2 )]ClO4 (11 ) identified, and its structure was determined by X‐ray diffraction. Complex11 contains a Pt → Ag [2.8147(1) Å] bond and a η 1 ‐Ag–C ipso (bzq) interaction [2.293(1) Å]. The electronic absorption and luminescence behaviors of1 –11 were investigated. The lower‐lying absorption bands of the mononuclear complexes are ascribed to ligand‐centered [ 1 IL, π–π* (bzq)] character mixed with some metal‐to‐ligand charge transfer [ 1 MLCT 5d(Pt) → π*(bzq)]. For the trinuclear complexes, these bands are assigned to 1 ILCT/ 1 MM′LCT [π–π*(bzq)]/d/s(Pt, Ag) → π*(bzq)] transitions and to mixed 1 MLCT/ 1 L′LCT [MLCT 5d(Pt) → π*(bzq)]/[L′LCT, Arf → bzq] for dinuclear complex11 on the basis of time‐dependent TD (DFT) calculations carried out on2, 4, 5, 9, 10, and11 Me in CH2 Cl2 . Only2 and the heteronuclear compounds are emissive in the solid state at room temperature; however, all of the complexes are emissive at 77 K (solids and glasses). In each case, the main phosphorescent emission seems to be due to a transition similar in character to the lowest‐energy electronic absorption. Abstract : Trimetallic [Pt(C6 F5 )(bzq)L2 Ag] + and bimetallic [(C6 F5 )(bzq)(PPh3 )PtAg(pyPh2 )] + clusters containing Pt–Ag bonds were prepared from [Pt(C6 F5 )(bzq)L] (bzq = 7, 8‐benzoquinolinate). These complexes have luminescent properties that were studied and interpreted with the help of time‐dependent DFT calculations.